EVALUASI MIKROSTRUKTUR KULIT TELUR ITIK PASCA FORMULASI KHITOSAN-ASAP CAIR SELAMA PENGASINAN - I N. S., MIWADA; HARTAWAN, M.; SUKADA, I K. (Majalah Ilmiah Peternakan; Vol 21 No 1 (2018): Vol 21, No 1 (2018), 2018)
This study aims at analyzing the ability of chitosan-formula liquid smoke to make innovation of curing times with penetration through the pores of duckling egg shells on the process of salting. A completely randomized design (CRD) was used with long curing treatment in 5, 10, 15, and 20 days. Besides, formula chitosan-liquid smoke with 20 g/l and 3% concentration were used in this experiment. The results showed that the curing of time up to 15 days gave the highest score (P<0.05) with good criteria. The quality of chemical in a long curing times gave significant differences (P<0.05) from indicators as of pH value, protein, and content of total phenol, and acids. The result of SEM (Scanning Electron Microscope) showed that formulation of chitosan-liquid smoke could give effect to a relatively open eggshells microstructure. It can be concluded that chitosan formulation with 20 g/l concentration and 3% of liquid smoke concentration can be effective at 15 days curing time.